La circulación de la clase política en Colombia: El congreso de la republica durante el frente nacional - Duque Daza, Javier (Sociedad y Economía, 2005)
This paper studies the circulation of the political class in Colombia during theperiod of Frente Nacional (1958-1974). First, the paper measures the degree ofcirculation of the institutionalized political class, both during the inter-electoral period and in comparison to the mean of the whole period under analysis. Second, it points to factors that procure that a political regime, in spite of serious democratic restrictions, is able to offer a high rate of circulation within the political class. In this perspective the paper analizes the role of faccionalism and of the presence of opposition parties with electoral success within the high circulation of Congress members. Third, the text accentuates the presence of various cliques within the Colombian political class, that fluctuate according to their stability within the Congress, their presence at the decisional level of the Congress, and their insertion within the managerial positions of the parties